Tectonic development of the Northwest Bonaparte Basin, Australia by using Digital Elevation Model (DEM) - Ali Wahid, Ahmed Mohamed Ahmed Salim, Gamal Ragab Gaafar, AP Wan, . (2016)
The Bonaparte Basin consist of majorly offshore part is situated at Australia's NW continental margin, covers an area of approx. 270,000 km 2. Bonaparte Basin having a number of sub-basins and platform areas of Paleozoic and Mesozoic is structurally complex. This research established the geologic and geomorphologic studies using Digital Elevation Model (DEM) as a substitute approach in morphostructural analysis to unravel the geological complexities